LANGUAGE STYLE IN FASHION ADVERTISEMENTS OF ONLINE VOGUE MAGAZINE - Irene Anggita Dennaya; Barli Bram (JOALL (Journal of Applied Linguistics and Literature), 2021)
In advertising, one of the purposes of communication is to offer a particular product. Advertisements display the advantages, features, and values of the products. This paper aimed to analyse the language styles used in online Vogue Magazine fashion advertisements. The data were collected by selecting ten advertisements collected from Vogue Magazine’s compilation entitled “The Fall 2020 Trends Vogue Edition Editors are Shopping This Season” published on 18 September 2020. The researchers employed mixed methods to analyse the language styles used in the fashion advertisements based on nine types of language styles proposed by Wells, Burnett, and Moriarty (1995). The results showed that there were three language styles found from ten online fashion advertisements in Vogue Magazine advertisements, namely the hard sell style (three times), soft sell style (three times), and mixed style or the combination of the hard sell and soft sell styles (four times). Each advertisement style has its specific features and functions in fashion promotion.